The Virtuous Drinker: Character Virtues as Correlates and Moderators of College Student Drinking and Consequences - Logan, Diane E. (2010)
OBJECTIVE: The present study examined the relationship between alcohol use and positive psychology’s character virtues(1) in a college student sample. Each of the virtues of wisdom, courage, humanity, justice, temperance, and transcendence were examined as protective factors and moderators of drinking consequences. PARTICIPANTS: This sample included 425 undergraduate students at a large Northwest University (69% female; 52% Caucasian, 34% Asian). METHODS: Participants completed paper and pencil questionnaires during October and November 2006 in exchange for extra credit in psychology classes. RESULTS: Higher temperance scores were associated with abstinence, lower risk drinking, and fewer consequences among heavy drinkers; both increased justice and transcendence were independently associated with abstinence only; and wisdom, courage, and humanity were not associated with any outcomes. CONCLUSIONS: The associations between virtues and college student drinking support a collaboration between addictive behaviors and positive psychology to address college student drinking and minimize consequences.